(In)visibility Before Privacy: A Theological Ethics of Surveillance as Social Sorting. (February 2014) - Stoddart, Eric
This article offers a theological ethics of surveillance in its form as social sorting. The skill of (in)visibility is deployed as an analytical device to critique the saliency of privacy rights-talk, given the focus of surveillance having shifted from a panoptic gaze to actionable intelligence. The claim is made that an ideology of normativity and the political categories of 'evil' and 'risky' persons can be addressed by the notions of relational knowledge (Muers), the resurrection of the non-person (Swinton) and the power of the future (Moltmann). Three biblical vignettes illustrate (in)visibility and offer imaginative responses.